Design and optimization of runner and gating systems for permanent mould casting - Roni Sahroni, Taufik; Kamaruddin, Mohammad Aizrulshah; Kasim, Mohd Shahir; Md Ali, Mohd Amran; Mohamad, Effendi; Ito, Teruaki (2014)
This paper presents the design and optimization of runner and gating systems for permanent mould casting. Fluid flow effect influences the casting quality. The design parameters for permanent mould casting were identified. The generation of runner and gating system were selected. There were four design concepts to simulate the static pressures, velocity magnitude,turbulence kinetic energy, internal energy and cell Reynolds numbers. Transient and turbulence flow model for LM6 material were applied to the design and simulation. The selection of design concept was introduced. The simulation result shows the design of runner and gating systems good agreement with the casting quality.